Optical electromagnetic antiferromagnetic flux with electroosmotic velocity in spherical Heisenberg group - Korpinar, Zeliha; Korpinar, Talat; Asil, Vedat (Elsevier Gmbh, 2022)
In this manuscript, we define antiferromagnetic microscale with electroosmotic velocity on spherical Heisenberg group. We construct optical electromagnetic spherical empty set (alpha) , empty set (t) , empty set (s) -flux by using electromagnetic flux empty set (alpha), empty set (t) , empty set (s) -density in cold plasma. We have simulated electric flux St-density and electroosmotic modeling with antiferromagnetic laminar flow. Finally, we obtain the total optical electric empty set (alpha), empty set (t) , empty set (s) -charge of closed St-surface on spherical Heisenberg group.
Keywords: Electromagnetic St-phase; St-density; Antiferromagnetic spin; Geometric St-optical fibers; Antiferromagnetic microscale